2020
DOI: 10.3390/mi11090841
|View full text |Cite
|
Sign up to set email alerts
|

Inkjet Printing on a New Flexible Ceramic Substrate for Internet of Things (IoT) Applications

Abstract: In this article, the optimization of printing properties on a new, flexible ceramic substrate is reported for sensing and antenna applications encompassing internet of things (IoT) devices. E-Strate® is a commercially available, non-rigid, thin ceramic substrate for implementing in room temperature and high-temperature devices. In this substrate, the printing parameters like drop spacing, number of printed layers, sintering temperature, and sintering time were varied to ensure an electrically conductive and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Flexible ceramics substrates are also another preference. Some flexible ceramics substrates developed today include zirconia‐based [ 210 ] and inorganic mica. [ 211,212 ] High strength and flat surface up to atomic scale is the requirement to obtain high crystalline thin‐film.…”
Section: Fabrication Of Flexible and Wearable Mxenes‐based Gas Sensin...mentioning
confidence: 99%
“…Flexible ceramics substrates are also another preference. Some flexible ceramics substrates developed today include zirconia‐based [ 210 ] and inorganic mica. [ 211,212 ] High strength and flat surface up to atomic scale is the requirement to obtain high crystalline thin‐film.…”
Section: Fabrication Of Flexible and Wearable Mxenes‐based Gas Sensin...mentioning
confidence: 99%
“…One important step to achieve high TCR of inkjet-printed temperature sensors is the sintering of the printed nanoparticles. High sintering temperatures increase the density and the conductivity of inkjet-printed nanoparticle structures due to higher driving forces during sintering [ 15 ]. Matthiessen’s rule states that the sensitivity of an electrical resistance to temperature only depends on the scattering of phonons [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other important sintering parameters to achieve high sintering densities are dwell time and heating rates. A dwell time of usually 10 to 30 min should be reached so that sintering can occur [ 15 , 17 ]. High heating rates are preferable, since slow heating rates can result in rounding of pores during the first phase of sintering [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this case where a metallic nanoparticlebased ink was printed on a non-porous surface, mechanical interlocking is the most dominant adhesion mechanism as there was no surface treatment done prior to printing. This is supported by Halonen et al [42], Niittynen et al [43] and Gopal Kirtania et al [44] who also reported that the sintering time and sintering duration are the most influential factors for adhesion improvement.…”
Section: Adhesion Classificationmentioning
confidence: 65%